2022
DOI: 10.3390/ijms231810289
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Changes in Intestinal Microorganisms and Effect of High Temperature on the Growth and Development of Bombyx mori Larvae

Abstract: Temperature is an important environmental factor affecting the growth and development of silkworm (Bombyx mori). To analyze the effect of intestinal microbes on silkworm in response to a high-temperature environment, this study used a combination of high throughput sequencing and biochemical assays to detect silkworm intestinal microbes treated with high temperature for 72 h. The results show that high temperature affects the intestinal microbes of silkworm and that there are sex differences, specifically, fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Microbial community analysis is a powerful tool in disease research [20]. In a previous similar study of the intestinal microbial community of insects, numerous microorganisms were found to live in the intestines of healthy insects, with the balance disrupted under specific environmental conditions, resulting in disease onset [21,22]. According to Koch's postulates, microbial community analysis is used in disease diagnosis because the initial condition of a disease-causing pathogen is "dominant" [23].…”
Section: Role Of Microbial Community In Inducing Sepsis In Silkwormsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbial community analysis is a powerful tool in disease research [20]. In a previous similar study of the intestinal microbial community of insects, numerous microorganisms were found to live in the intestines of healthy insects, with the balance disrupted under specific environmental conditions, resulting in disease onset [21,22]. According to Koch's postulates, microbial community analysis is used in disease diagnosis because the initial condition of a disease-causing pathogen is "dominant" [23].…”
Section: Role Of Microbial Community In Inducing Sepsis In Silkwormsmentioning
confidence: 99%
“…Ultimately, in our microbial community analysis, shown in Figure 3, silkworms grown under the same conditions showed marked differences in the microbial communities according to the presence or absence of sepsis because of differences in the immune, nutritional, and physiological factors of each individual and S. nematodiphila introduced from the external environment. This is believed to be because the introduction of these bacteria disrupted this balance [21]. In fact, in the microbial community analysis of healthy silkworms, S. nematodiphila was not present in the intestines.…”
Section: Role Of Microbial Community In Inducing Sepsis In Silkwormsmentioning
confidence: 99%
“…The growth and development of the domestic silkworm model established in a conventional environment is too fast and the survival period of the model is too short, which leads to inadequate observations of the developmental stages of the disease. Temperature is the most important factor that affects silkworm development, since changes in the external environmental temperature influence the body temperature of silkworms, thereby affecting their growth and development (Sun et al, 2022). Different environmental factors exert diverse effects on the growth and development of silkworms.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic factors, lifestyle, and natural environment such as diet and ambient temperature ( Gould et al, 2018 ; Osadchiy et al, 2019 ) affect the composition of microorganisms ( Zmora et al, 2019 ). Changes in temperature can lead to changes in the function of intestinal flora, thus affecting the digestion and absorption of food ( Sun et al, 2022 ). In a certain temperature range, the increase in temperature helps in colonizing some beneficial bacteria in the intestinal tract and promotes the digestion and absorption of the host.…”
Section: Introductionmentioning
confidence: 99%